Effect of Reynolds Number and Temperature on Water Heater Loss Coefficient - VAIRAVAN NACHIAPPAN, VAIRAVAN MANIKANDAN; En. Ahmad Fu'ad Idris; Mohd Azwir Azlan (Research Progress in Mechanical and Manufacturing Engineering, 2026)
The Loss coefficient of the heater determines how much pressure drop occurs as fluid flows through it. Accurate estimation of the loss coefficient of the heater is essential for optimizing thermal system performance. A higher loss coefficient of the heater indicates greater resistance to flow, which can reduce system performance. To determine the effect of Reynolds Number and temperature on water heater loss coefficient, an experimental apparatus was designed and fabricated to measure pressure differences and flow rates across a water heater system. Tests were conducted based on two different conditions which is temperature constant, different volumetric flowrate and different temperature, constant volumetric flowrate. The experimental findings demonstrate that the heater’s loss coefficient exhibits a direct proportionality to the Reynolds number. This relationship suggests that flow regime and velocity play a dominant role in determining the hydraulic resistance of the heater. In contrast, variations in fluid temperature were observed to have no measurable influence on the loss coefficient. This indicates that thermal effects, within the tested range, do not significantly alter the fluid’s interaction with the heater geometry. This outcome highlights the dominance of flow dynamics over thermal influences in determining hydraulic resistance. These findings provide a useful basis for optimizing heater design and improving efficiency in thermal fluid systems.